A NIR light-triggered drug delivery system using core–shell gold nanostars–mesoporous silica nanoparticles based on multiphoton absorption photo-dissociation of 2-nitrobenzyl PEG. Issue 61 (11th July 2019) - Hernández-Montoto, Andy; Gorbe, Mónica; Llopis-Lorente, Antoni; Terrés, José Manuel; Montes, Roberto; Cao-Milán, Roberto; Díaz de Greñu, Borja; Alfonso, María; Orzaez, Mar; Marcos, María Dolores; Martínez-Máñez, Ramón; Sancenón, Félix
Abstract : Gold nanostars coated with a mesoporous silica shell and functionalised with PEG containing photolabile 2-nitrobenzyl moieties released doxorubicin after NIR light irradiation. Abstract : Gold nanostars coated with a mesoporous silica shell and functionalized with poly(ethylene glycol) containing photolabile 2-nitrobenzyl moieties are able to release doxorubicin after NIR light irradiation at low power irradiance via a multiphoton absorption photo-dissociation process.